Effect of Calcium Triphosphate Cement on Proximal Humeral Fracture Osteosynthesis: A Cadaveric Biomechanical Study. (August 2013) - Kennedy, Jim; Molony, Diarmuid; Burke, Neil G; FitzPatrick, David; Mullett, Hannan
Purpose: To evaluate the effect of filling a central humeral bone void with calcium triphosphate cement on the strength and stability of an osteosynthesis in elderly cadavers. Methods: 14 fresh cadaveric shoulder specimens obtained from 11 donors (mean age, 91.5 years; mean body weight, 61 kg) were divided into 2 age- and sex-matched groups. A standardised 3-part proximal humeral fracture with a central bone void was created in each specimen. Each specimen was reduced and fixed with a locking plate. In half the specimens the central bone void was packed with calcium triphosphate cement. The intra-fragmentary motion and the load and mode of failure were recorded. Results: Respectively in the test group and controls, the intra-fragmentary motion was 1.0 and 6.4 mm, and the peak displacement at the 500 N load was 1.8 and 9.1 mm. The Cohen's d was 1.6 to 2.7 for all load steps, indicating a large effect of the calcium triphosphate cement on strength and stability. The mean difference in the failure load was 300 N (p<0.05). Conclusion: Construct stability and failure load improved significantly when the central humeral bone void was filled with calcium triphosphate cement.